Síndrome de burnout entre médicos e acadêmicos do curso de medicina: revisão de literatura - Ferreira, Eber Junior Gomes (2020)
Introduction: Burnout Syndrome is characterized by physical and psychological exhaustion marked by mental exhaustion, depersonalization and reduced personal fulfillment. This study aims to build an integrative literature review on the prevalence of Burnout Syndrome among doctors and medical students based on published scientific articles. Methodology: research was carried out in the databases Science, Lilacs and PubMed with the following descriptors: “Burnout Syndrome”, “physicians”, “doctors” e “students” between the years 2009 to 2019 in Portuguese . A total of 287 articles were found, of which 28 articles were selected by reading titles and abstracts, according to the criteria for inclusion of articles used by Brazilian researchers between the years 2009 to 2019, whose central theme is the current work proposal. The requirements used to exclude those who were affected by other psychiatric syndromes that do not have Burnout Syndrome, as well as those that include professionals other than doctors and students from other different undergraduations. Results and Discussion: The results found in the incidence of Burnout Syndrome in this population are greater in the general population and in other academic groups. The main causes pointed out in the studies were the biggest ones caused by psychiatric disorders, substance abuse and suffering related to experiences of the profession, such as heavy workload, sleep deprivation, difficulties with patients, financial difficulties, information overload and family distance. Conclusions: The prevention of Burnout syndrome is possible, but the problem has been neglected. It carries out other studies on the topic to promote and apply prevention policies, in addition to specific treatment for this population.